The effect of nutritional behavior pattern education to toddler mothers on the nutritional pattern improvement of toddlers & mothers performance - akram sadat Sadat Hoseini; sosan Samiee; nagmeh Razaghee (Tehran University of Medical Sciences, 2008)
Background & Aim: Nutrition is a very important factor in toddler age growth. Getting started the first steps of the children with family in this period shows the necessity of paying attention to the correct nutritional behaviors. Therefore this research has been conducted for assessing the effect of nutritional behavior model on the quality of toddler;aposs nutrition and performance of their mothers.Methods & Materials: This research is a semi-experimental study, in which sixty six children (12-36 months old) were selected from two health care centers in the southern part of Tehran. The subjects were selected using non probability-convenient sampling method. The data gathering tool was 3 questionnaires: 1. Mother and child demographic characteristics 2. Mother;aposs function assessment tool about toddler;aposs behavior during feeding 3. Reminding tool of 24 hours food. The tools were filled in using interviews. Then nutritional behavior model was instructed in a workshop during 2 days, 3 hours a day. After the intervention data were recollected again and were analyzed by descriptive and inferential statistics.Results: The results showed a significant difference in mother;aposs function about toddlers nutritional behavior during nutrition before and after the intervention (P<0.001). Also a significant difference was seen in the toddlers nutrition pattern before and after the intervention (P<0.05).Conclusion: Based on the research findings it can be concluded that nutritional behavior model is effective in improving the pattern of toddler;aposs nutrition and in increasing mothers;apos knowledge related to a correct function on toddler;aposs behavior during feeding. Therefore educational plan to mothers on correct nutritional behaviors is suggested in order to improving the quality of toddler;aposs nutrition.